Transitions in social media use and social media use for transition: A survey study of the shift from high school to college - Dennen, Vanessa P.; Bagdy, Lauren M. (Proceedings of the International Conference on Networked Learning, 2024)
High school and college students are known to be heavy users of social media. Much of their use is focused on peer social interactions and entertainment, but social media is also a potential platform for informal networked learning. In this study, we examine how college students used social media to learn about and prepare for college, how they use it in the university context, and how their social media use has changed as they mature and transition from one educational setting to another. Undergraduate students at a large public research university completed an online survey about their social media uses and perceptions. In terms of using social media to support the high school to college transition, preliminary findings show that for many students social media provided a valuable source of information about colleges, and in particular helped them plan and begin to build their social and activity networks in their new setting. Once at college, social media continued to help provide connections, serving as a source of information about campus events and supporting social connections. Social media was less frequently used as a means of networking with instructors. Many students noted that their use of social media had changed in meaningful ways as they transitioned to college. These students indicated that their networks were now different, that their attitudes and uses had matured, and that they were better able to use their social media networks as a platform for awareness and change. Whether they perceived meaningful changes in their use of social media across the transition, most participants alluded to a desire to minimize drama, social comparison, and other ill effects of social media. As data analysis continues, we will be exploring differences across platforms and relationships in college-related social media use based on intensity of use and sense of belonging. The study has implications for how institutions offer and support the development of social media networks among prospective and current students and provides insight into mindsets that can support or inhibit greater use of social media as a platform for informal networked learning as youth transition from high school to college and eventually on to careers.